2013
DOI: 10.1159/000355247
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Amusement Park Rides on Programmable Shunt Valve Settings

Abstract: Background: Magnetically programmable shunt valves are susceptible to environmental factors including magnetic fields and accelerative forces. It is unknown if rollercoasters with or without magnetic brakes or linear induction motors (LIMs) are capable of altering the setting of a programmable shunt valve. Methods: Two different valve types (type A, n = 10; type B, n = 9) were tested at varying resistance settings in 2 trials on 6 different amusement park rides including 2 rides with LIMs, 2 rides with magneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…[ 2 3 4 11 14 ] Even amusement park rides can cause maladjustment of valves. [ 10 ] Despite these risks, programmable valves, when compared to nonprogrammable shunts, are found to be associated with a significant decrease in complications regarding over or underdrainage, as well as a reduction in overall complications. [ 1 13 ] Regulating the amount of flow is important because, as in the presented case, over-drainage can lead to problems such as subdural bleeds, craniosynostosis, and intracranial hypotension.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 3 4 11 14 ] Even amusement park rides can cause maladjustment of valves. [ 10 ] Despite these risks, programmable valves, when compared to nonprogrammable shunts, are found to be associated with a significant decrease in complications regarding over or underdrainage, as well as a reduction in overall complications. [ 1 13 ] Regulating the amount of flow is important because, as in the presented case, over-drainage can lead to problems such as subdural bleeds, craniosynostosis, and intracranial hypotension.…”
Section: Introductionmentioning
confidence: 99%
“…In the study conducted with Strata, Codman and Sophy valves, it was found that cell phones could theoretically affect the valves and Strata was more sensitive than the others (9) . In a study measuring the magnetic relationship between the tablet computer and the programmable VPS valve, it was found that the valve setting changed 58% at a distance of less than 1 cm and that the valve was not affected at distances greater than 5 cm (10) . In the study, which calculated the effect of Magnetic toys on Strata II small (Medtronic Inc.), Codman Judge (Codman & Shurtleff), and Polaris (Sophysa) programmable VPS valves; it has been reported that the Polaris valve setting did not change in any way, the adjustment of the Codman valve up to 30 mm and the Strata valve up to 50 mm are affected (10) .…”
Section: Discussionmentioning
confidence: 99%
“…The Earth's inherent MF is on the order of 50 µT or 0.5 G. 3 The values generated by magnetometers are in units of micro-Teslas (µT). The ambient or baseline measurement on magnetometers across tested smartphone devices in the study ranged between 20 and 100 µT.…”
Section: Calibration Of Smartphone Magnetometermentioning
confidence: 99%
“…Unnoticed external forces can have an influence over PV mechanisms and modify the opening pressure setting. 3 MFs produced by many devices can often be a concern for Evaluation of smartphone-integrated magnetometers in detection of safe electromagnetic devices for use near programmable shunt valves: a proof-of-concept study patients and parents of children with shunt-treated hydrocephalus who have PVs, since strong MFs from external magnetic sources and implanted medical devices that use magnets can cause an unintended change in their valve setting. Although devices from the most recently developed generation have been designed with greatly improved resistance to MFs, [4][5][6][7][8] devices sensitive to field strengths of more than 90 Gauss (G) are still commonly implanted and will exist in patients for decades to come.…”
mentioning
confidence: 99%